(untitled) (Cadernos de Filosofia Alemã: Crítica e Modernidade, 2021)
Why is the theme of humanism and anti-humanism so prevalent in Ruy Fausto's work, following his intellectual journey from beginning to end? The aim of this article is to analyze this theme in several writings of the author, in order to understand such relevance. However, it is impossible to do this without addressing at least part of the enormous variety of problems that Fausto discussed throughout his work, in the fields of logic, philosophy of history, ontology, philosophical anthropology, ethics and politics. In the end, what is revealed is the purest expression of dialectics as a web of critical thinking that takes complexity and subtlety to the maximum and dismantles, one by one, the most diverse unilateral positions. Thus, it is the field of dialectical critique itself that will expand beyond the Marxist critique of capitalism.